# Solve:- 3(2 − x) + 4 = 7 + 3(x − 5)

## Answers

Answered by

0

6-3x+4=7+3x-15

6+4-7+15=3x+3x

10-7+15=6x

3+15=6x

18=6x

18÷6=x

3=x

**That's**** ****All**

**Thank ****you**

**I ****hope**** ****it**** will**** ****help**** you**

Answered by

132

**Step-by-step explanation:**

__Q____u____e____s____t____i____o____n____:__

Solve:- 3(2 − x) + 4 = 7 + 3(x − 5)

__S____o____l____u____t____i____o____n____:__

➨ 3(2 − x) + 4 = 7 + 3(x − 5)

➨ 3 X 2 + 3 X -x + 4 = 7 + (3 X x ) + 3 X -5

➨ 6 + (-3x) + 4 = 7 + 3x + (-15)

➨ 6 - 3x + 4 = 7 + 3x - 15

◆ **B****r****i****n****g**** ****t****h****e**** ****numerals ****together ****a****n****d**** ****perform ****t****h****e**** ****calculations****. **

➨ 6 + 4 -3x = 7 - 15 + 3x

➨ 10 - 3x = -8 + 3x

➨ 10 + 8 = 3x + 3x

➨ 18 = 6x

➨ 18/6 = x

➨ 3 = x

__M____o____r____e____ ____Informatio____n____:__

__B____O____D____M____A____S____ ____S____T____A____N____D____S____ ____F____O____R____ ____:__

**B**** ****-**** ****B****r****a****c****k****e****t**** **

**O**** ****-**** ****O****f**** **

**D**** ****-**** ****Division **

**M**** ****-**** ****Multiplication **

**A**** ****-**** ****A****d****d****i****t****i****o****n**** **

**S**** ****-**** ****Subtraction **

__B____O____D____M____A____S____ ____R____u____l____e____s____:__

✪ (-) (+) = (-)

✪ (+) (+) = (+)

✪ (-) (-) = (+)

ⓦⓔ ⓐⓛⓦⓐⓨⓢ ⓢⓞⓛⓥⓔ ⓢⓤⓜⓢ ⓛⓘⓚⓔ ⓣⓗⓔⓢⓔ ⓤⓢⓘⓝⓖ ⓑⓞⓓⓜⓐⓢ.

Similar questions